Safety and efficacy of extracorporeal shock wave lithotripsy vs. flexible ureteroscopy in the treatment of urinary calculi: A systematic review and meta-analysis - Lv, Guangda; Qi, Wenqiang; Gao, Han; Zhou, Yongheng; Zhong, Minglei; Wang, Kai; Liu, Yunxing; Zhang, Qiang; Zhou, Changkuo; Li, Yan; Zhang, Lingling; Zhang, Dongqing (Frontiers in Surgery, 2022)
Objective To compare the safety and efficacy of extracorporeal shock wave lithotripsy (ESWL) and flexible ureteroscopy lithotripsy (f-URS) in the treatment of urinary tract stones. Methods We systematically searched PubMed, Embase, and Cochrane for literature comparing ESWL with f-URS. The primary outcomes we focused on were stone-free rate (SFR) and complications; the secondary outcome events were operation time, hospital days, retreatment rate, number of sessions, auxiliary procedures rate. We used review manager version 5.4.1 and STATA version 14.2 for meta-analysis. Results Seventeen studies with a total of 2265 patients were included in meta-analysis, including 1038 patients in the ESWL group and 1227 patients in the f-URS group. The meta-analysis indicated that patients in the f-URS group had higher (SFR) than EWSL group (OR: 2.00, 95% CI: 1.29 to 3.12, p=0.002). Besides, we found there was no significant difference between two treatments in complications rate (OR: 1.08, 95% CI: 0.85 to 1.37). And we found that the retreatment rate and the auxiliary procedure rate in the f-URS group were significantly lower than that in the ESWL group (OR: 0.08, 95% CI: 0.02 to 0.24, p <0.00001) (OR: 0.30, 95% CI: 0.11 to 0.83, p =0.02). Moreover, the number of sessions of F-URS group was significantly less than that in the ESWL group (MD: -1.96, 95% CI: -1.55 to -0.33, p =0.003). But the operation time and hospital days in the f-URS group were significantly longer than that in the ESWL group (MD: 11.24, 95% CI: 3.51 to 18.56, p=0.004) (MD: 1.14, 95% CI: 0.85 to 1.42, p<0.00001). Conclusion For 1-2CM urinary stones, f-URS can achieve a higher SFR than ESWL, while having lower retreatment rate, number of sessions, auxiliary procedures rate. For urinary stones <1CM, there was no significant difference in SFR between ESWL and f-URS. ESWL has a shorter operative time and hospital stay than f-URS.